Geochemical analysis of sediment samples for forensic purposes: characterisation of two river beaches from the Douro River, Portugal. Issue 2 (3rd March 2020) - Madureira-Carvalho, Áurea; Ribeiro, Helena; Newman, Gareth; J. Brewer, Mark; Guedes, Alexandra; Abreu, Ilda; Noronha, Fernando; Dawson, Lorna
ABSTRACT: In the context of the forensic sciences, geochemical data can give important information as to the sample origin or help to refine and narrow the probable origin. The current study employs geochemical data with multivariate analyses to examine the potential of some elements usually employed in environmental studies (As, Cd, Co, Cr, Cu, Hg, Ni, Pb, Zn and Mn) in the spatial and temporal discrimination of sediment samples from two river beaches. For one year, samples were collected along profiles perpendicular to the river and analysed using Inductively Coupled Plasma – Mass Spectrometry (ICP-MS) and Inductively Coupled Plasma – Optical Emission Spectroscopy (ICP-OES). This study shows that the geochemical analysis allows the discrimination of two river beaches with similar geo-environmental context and also discrimination between samples along the profiles from the same beach. In each beach profile the majority of the analysed elements did not show significant differences between each season of the year, showing that seasonality may not affect that identification of source. Results show that the geochemical signature is very specific to each area and therefore useful to establish the provenance of a questioned sample. This could also be useful for the determination of assignment of environmental contamination.